Tetrandrine ameliorates cognitive impairment via inhibiting astrocyte-derived S100B activation in a rat model of chronic cerebral hypoperfusion. (July 2013) - Chen, Lianlian; Chen, Lixue; LV, Yanling; Cui, Zhiwei; Bei, Gui; Qin, Guangcheng; Zhou, Jiying; Ge, Tan
Abstract : Objectives: To investigate the effects of tetrandrine (Tet) on cognitive impairment induced by chronic cerebral hypoperfusion and its potential anti-inflammatory mechanism by modulating the expression of S100B, interleukin-1 beta (IL-1beta), tumor necrosis factor-alpha (TNF-alpha), and inducible nitric oxide synthase (iNOS). Methods: Chronic cerebral hypoperfusion was induced by ligation of the bilateral common carotid arteries for 8 weeks. Rats were treated with Tet (10 mg/kg or 30 mg/kg) intraperitoneally every 3 days for 4 weeks. Cognitive function of rats was evaluated by the Morris water maze. Hematoxylin eosin (H & E) and Nissl staining were used to observe neuronal damage in the hippocampal CA1 region. Immunofluorescence, quantitative real-time polymerase chain reaction (QT-PCR), and western blot were performed to measure S100B, IL-1beta, TNF-alpha, and iNOS levels in the CA1 region of chronic cerebral hypoperfusion rats. Results: The Tet-treated group significantly decreased the escape latency of chronic cerebral hypoperfusion rats in finding the hidden platform ( P <0·05). Compared with the 2-VO (two-vessel occlusion) group, more neurons with regular morphology and/or Nissl bodies in the hippocampus were observed in the Tet-treated group, suggesting attenuated neuronal damage and degeneration. Additionally, S100B, IL-1beta, TNF-alpha, and iNOS levels were significantly ( P <0·05) decreased in the CA1 region of the chronic cerebral hypoperfusion affected rats treated with Tet. Conclusion: Our results found that Tet could improve cognitive impairment in the chronic cerebral hypoperfusion rats. Tetrandrine may be a novel and promising candidate for future treatment and/or prevention of chronic cerebral hypoperfusion via inhibiting S100B activation and decreasing the expression of IL-1beta, TNF-alpha, and iNOS in the hippocampal CA1 region.